Pembangunan Sistem Informasi Pemberian Kredit Pada Koperasi Mekarsari Dengan Metode Rapid Application Development - Nur Hidayati; Ety Nurhayaty (LPPM Universitas Bina Sarana Informatika, 2019)
The cooperative is a business entity that is very well known by pro people, because the cooperative is group of individuals who run its business based on family principle, Pancasila and the Undang-Undang 1945. The cooperatives development in Indonesia indicates a positive trend and known by the public. One of them is Cooperative Mekarsari. This filled Mekarsari cooperative is getting better every day. Cooperative Mekarsari provided many services to members, one of them is about the granting of credit or loans. Granting of credit given is usually devoted to the retirement, although not close the possibility of members who are not retired can ask loan. However, data processing in granting credit Cooperative Mekarsari is still done manually, giving rise to some problems, such as the granting of credit or loans still recorded using handwritten into the book loans, still merge the recording of data between loan and installment, there is no limitation work space that allows the data become no secret. By looking at it, then this requires the existence of a Cooperative system to facilitate development in the processing of the data and provide services to its members. And to assist in the process of developing such a system, it is necessary to use an appropriate method, i.e. the Rapid Application Development method. The expected results of this form system development, program application is expected to resolve the existing problems in Cooperative Mekarsari. Keywords: program application, cooperation, RAD, loan